Immunodominance hierarchy of influenza subtype-specific neutralizing antibody response as a hurdle to effectiveness of polyvalent vaccine - Hoyoung Lee; Eun Hyoung Shim; Sooseong You (Taylor & Francis Group, 2018)
Strengthening of immunodominance hierarchy of influenza subtype-specific neutralizing antibody response by annual polyvalent vaccinations could increase the variation of vaccine effectiveness by subtype. Therefore, we suggest the assessment of neutralizing antibody titer prior to seasonal vaccination and recommend the inoculation of only strains lower than protective levels.